2020
DOI: 10.2183/pjab.96.033
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial γ-glutamyltranspeptidases, physiological function, structure, catalytic mechanism and application

Abstract: γ-Glutamyltranspeptidase (GGT) has been widely used as a marker enzyme of hepatic and biliary diseases and relations between various diseases and its activity have been studied extensively. Nevertheless, several of its fundamental enzymatic characteristics had not been elucidated. We obtained homogeneous preparation of GGTs from bacteria, characterized them, and elucidated its physiological function that is common to mammalian cells, using GGT-deficient E. coli . Prior to GGT of all livi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 107 publications
(146 reference statements)
0
12
0
Order By: Relevance
“…In this study, a phylogenetic analysis indicated that the gene of BaGGT and Bacillus GGT genes belonged to the same branch, on which basis we speculated that the primary structure of BaGGT was similar to that of known Bacillus GGTs . We aimed at providing a suitable expression host for this enzyme; a recombinant expression system for BaGGT in L.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In this study, a phylogenetic analysis indicated that the gene of BaGGT and Bacillus GGT genes belonged to the same branch, on which basis we speculated that the primary structure of BaGGT was similar to that of known Bacillus GGTs . We aimed at providing a suitable expression host for this enzyme; a recombinant expression system for BaGGT in L.…”
Section: Discussionmentioning
confidence: 94%
“…In this study, a phylogenetic analysis indicated that the gene of BaGGT and Bacillus GGT genes belonged to the same branch, on which basis we speculated that the primary structure of BaGGT was similar to that of known Bacillus GGTs. 35 We aimed at providing a suitable expression host for this enzyme; a recombinant expression system for BaGGT in L. lactis (pNZ8048-sp usp45 -ggt Δsp -6his) was constructed. In addition, L. lactis is a well-known heterologous host with several advantages such as a reduced number of extracellular secreted proteins and proteases, which simplifies production and purification or the protein of interest and is an available toolbox for molecular manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…18 Many amino acids, peptides, and amines can be γ-glutamyl acceptors of bacterial GGT to synthesize γ-glutamyl compounds. 19,20 For example, enzymatic methods for synthesizing L-theanine (γglutamylethylamide), 21−23 γ-D-Glu-L-Trp, 24 γ-Glu-Val, 18,25 γ-Glu-Phe, 26 and γ-Glu-Gln 27 have been reported. We previously reported that valylglycine (Val-Gly) was the best γ-glutamyl acceptor for E. coli GGT among dipeptides whose C-terminal side was glycine; 28 therefore, E. coli GGT is considered to be a suitable enzyme for synthesizing γ-Glu-Val-Gly when Val-Gly is used for the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…As the transpeptidation reaction of Escherichia coli GGT was activated by several cations at alkaline pH, the production yield of γ-Glu-Val increased approximately 1.5 times by the addition of 50 mM MgCl 2 to the reaction mixture after 3 h of incubation . Many amino acids, peptides, and amines can be γ-glutamyl acceptors of bacterial GGT to synthesize γ-glutamyl compounds. , For example, enzymatic methods for synthesizing l -theanine (γ-glutamylethylamide), γ- d -Glu- l -Trp, γ-Glu-Val, , γ-Glu-Phe, and γ-Glu-Gln have been reported. We previously reported that valylglycine (Val-Gly) was the best γ-glutamyl acceptor for E.…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme Ggt catalyzes the transfer of γ-glutamyl groups from donor molecules, most notably glutathione, to target or acceptor substrates consisting of amino acids, peptides or even water. Although Ggt has been implicated in the metabolism of glutathione and cysteine in some bacteria [ 36 ], little is known on the biological importance of this enzyme in Pseudomonas , including any potential role it may have in glutamate-related metabolism.
Fig.
…”
Section: Discussionmentioning
confidence: 99%